Koordinasi Penyelenggaraan Tugas Pembantuan di Kabupaten Bangka - Ayi Karyana (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2012)
The study aims to describe and analyze: (1) coordinate the implementation of co-administration in Bangka Regency; and (2) obtain a picture of the coordination function implemented in co-operation in the Regency of Bangka. The method used in this research is descriptive analysis on the basis of an interpretive approach. The results showed, in co-coordinating the implementation of Bangka regency between the Local Government Unit (SKPD) as the executor of the affairs of Co-administration (TP) and that the coordination of development planning, and funders (Provincial and Central) are not well coordinated. In the sense of coordination is still weak, it does not function according to the procedure that should be. Lack of coordination can lead to programs and activities of TP can not fully achieve the goals, and objectives are clear, in addition to the cost requirements, facilities and infrastructure, resource requirements needed to ensure the success of the TP has not been properly analyzed and measured in accordance with local capabilities.